MEMBUMIKAN ZAKAT: DARI TAABBUDI MENUJU TAAQQULI - Fakhruddin, Fakhruddin (Fakultas Syariah, 2011)
AbstrakZakat is worship maliyah ijtimaiyyah. This means that in addition to a religious charity that is vertical (habl min Allah), as well as horizontal (habl min al-nas). As a worship that is vertical, including worship mahdhah charity that does not receive a â€œdiscussionâ€ (gair qobil li al-niqas). Therefore, the consequences will lose their elan vital charity and experiencing stagnant, despite the fact that charity has a very big opportunity in improving the welfare of Muslims, especially the poor. Seeing a huge opportunity zakat, the alms should not only be placed in positions that are taâ€™abbudi mahdhah worship only, but also put in a position that is taâ€™aqquli muamalah. With zakat placed on taâ€™aqquli position, then the development and utilization of zakat will be conducted in accordance with the circumstances and conditions so that truly righteous era wa li kulli eat, either in relation to expensive al-zakah/wi â€˜a al-zakah (object subject zakat), mustahiq al-zakah (the person entitled to receive zakat), and the pattern of distribution of zakat.Â Zakat adalah ibadah maliyah ijtimaiyyah. Artinya bahwa zakat disamping merupakan ibadah yang bersifat vertikal (habl min Allah), juga bersifat horizontal (habl min al-nas). Sebagai ibadah yang bersifat vertikal, zakat termasuk ibadah mahdhah yang tidak menerima â€œdiskusiâ€ (gair qobil li al-niqas). Oleh karena itu, maka konsekuensinya zakat akan kehilangan elan vitalnya dan mengalami stagnan, meskipun sebenarnya zakat mempunyai peluang yang sangat besar dalam meningkatkan kesejahteraan umat Islam, terutama fakir miskin. Melihat peluang zakat yang sangat besar tersebut, maka zakat mestinya tidak hanya ditempatkan pada posisi ibadah mahdhahÂ yang bersifat taâ€™abbudi semata, akan tetapi diletakkan juga pada posisi muamalah yang bersifat taâ€™aqquli. Dengan ditempatkannya zakat pada posisi taâ€™aqquli, maka pengembangan dan pendayagunaan zakat akan bisa dilaksanakan sesuai dengan situasi dan kondisi sehingga betul-betul shalih li kulli zaman wa makan, baik menyangkut mahal al-zakah/wiâ€™a al-zakah (obyek yang dikenai zakat), mustahiqÂ al-zakah (orang yang berhak menerima zakat), maupun pola distribusi zakat.Kata Kunci: zakat, taâ€™abbudi, taâ€™aqquli